Assesing Speaking Skills through the Implementation of TBLA in a Group of Second Graders (2018)
ABSTRACT: This action research explored the usefulness of implementing Task-based Language Assessment (TBLA) to help assess second graders’ speaking skills at a public school in Medellin. To do this, I designed and implemented a task about food to help students do an oral presentation about their likes and dislikes, and thus assessing their speaking skills. Data collection of this project included interviews, a survey, journals, and students’ artifacts. Findings showed that TBLA helped the students to have a better performance in their task since they were able to connect the different topics and be more prepared to face the final assessment. Furthermore, group work was a meaningful strategy for students to gain confidence during the development of the task.